MARKETING ACTIVITIES OF FITNESS SERVICE PROVIDERS IN THE NORTHERN GREAT PLAIN REGION - Müller, Anetta; Bácsné Bába, Éva; Pfau, Christa Sára; Bartha, Éva Judit; Molnár, Anikó; Pető, Károly (Acta Carolus Robertus, 2020)
As fitness services are suitable for compensate the disadvantageous effects of sedentary lifestyle, the number of studies which focus on the sport services’ demand and consumer motivation has significantly increased. Supply is also an area worth exploring, accordingly researchers conducted research studies primarily connected to the quality of service. Relatively few researches were focused on investigating the activities and characteristics of companies that operate fitness centers. Therefore, in our research we undertake the mapping of the entrepreneurial activity of companies providing fitness services in the Northern Great Plain region (N = 31). This study demonstrates that how important is the conscious use of marketingmix elements by service providers. Our results prove that the providers follow fitness trends and use the related information during product development. Thus, trend-oriented supply development is a key element in their marketing activities. Besides providing basic services, they also focus on complementary services (e.g. wellness facilities), which complement various workouts effectively. In addition to responding to changing consumer needs, service development often involves the pursuit of uniqueness. Their pricing is based on the strategy of adopting prices and competitor-oriented pricing. In terms of their promotional activities and sales channels, they prefer modern sales opportunities, especially online marketing to traditional tools and places.